Modernisasi Pangan Khas Minangkabau Palai Bada dengan Implementasi Inovasi pada Pengolahan dan Pemasaran - Ediset Ediset; Rian Hidayat; Taufiq Ihsan; Weriantoni Weriantoni; Amrizal Anas (Institut Pertanian Bogor, 2023)
The Community Partnership Program (CPP) to help businesses grow and develop is carried out in the Panas Minder group (Palai Bada Khas Minangkabau Moderized) which is located in Pauh District, Padang City. The product of Panas Minder's business is typical Minangkabau Palai Bada food, the product is still being processed and marketed traditionally so that the product does not last long and only has a local market share. The objectives of the activities are to improve the processing of Palai Bada products by implementing innovation in the combustion processes, and improve the marketing strategy of Palai Bada products by adopting digital marketing. The mentoring methods used to assist partners are field meetings and business meeting. The results of the coaching activities are partners have adopted combustion innovationsusing modern Furcase and Panas Minder partners have been trained and guided to take advantage of digital marketing by creating websites and official Instagram lines.